2010
DOI: 10.1111/j.1552-6569.2010.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone-Induced Toxic Leukoencephalopathy: Diagnosis and Follow-up by Magnetic Resonance Imaging Including Diffusion-Weighted Imaging and Apparent Diffusion Coefficient Maps

Abstract: Lesion pattern included subtle cerebellar involvement, mainly reversible extensive bilateral and symmetric brain involvement, cystic degeneration in the periventricular regions, sparing of corpus callosum and subcortical U-fibers, development of diffuse brain atrophy, and clear-cut clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 9 publications
(22 reference statements)
3
33
0
Order By: Relevance
“…Methadone-induced brain toxic leukoencephalopathy is reported in several cases with decreased level of consciousness [Salgado et al, 2010; Cerase et al, 2011; Bileviciute-Ljungar et al, 2014]. In addition, there is a cerebellar and basal ganglia involvement in methadone overdose as well [Corre et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Methadone-induced brain toxic leukoencephalopathy is reported in several cases with decreased level of consciousness [Salgado et al, 2010; Cerase et al, 2011; Bileviciute-Ljungar et al, 2014]. In addition, there is a cerebellar and basal ganglia involvement in methadone overdose as well [Corre et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…The results of Li et al (2016) suggested that methadone damages the integrity of the white matter of long‐time consumer of methadone in a dose‐dependent pattern . The radiological studies revealed that methadone in high concentration and long‐term consumption influences on the structure of the brain in the cerebellum, basal ganglia, and deep white matter of the cerebral hemispheres . For methadone, two signal paths have been suggested: one for binding to opioid receptors and another for acting as an antagonist in NMDR .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous other drugs of abuse have been associated with toxic leukoencephalopathy to a lesser extent. These include the psychoactive drug 2C-E "Europa" [15], oxycodone [24], and methadone [25,26].…”
Section: Discussionmentioning
confidence: 99%